Home fire protection in the wildland urban interface: the landowner's role in fire prevention - Firewise Community Prevention Partnership, author (Colorado State University. Libraries, 2007)
Wildfire hazards exist on most forested homesites. Many hazards can be reduced to acceptable levels by following fire wise guidelines.
CSFS rev #142-399.
Keywords: fire prevention; wildfires; fire protection engineering; fire safety; natural resources